The GCC Banking Sector : Topography and Analysis - Khamis, May (IMF Working Papers; Working Paper ;, 2010)
In this paper, we analyze the evolution of the Gulf Cooperation Council (GCC) banking sectors in the six member countries including ownership, concentration, cross-border linkages, balance sheet exposures and risks, recent trends in credit growth, and financial soundness. We identify risks to the banking sector's financial stability in the context of the current global crisis and their mitigating factors.